Statistical Yearbook for Latin America and the Caribbean 2013 - United Nations (United Nations, 2014)
This publication presents a set of basic statistics on the economic, sociodemographic and environmental situation of the region during a specific time period. This edition of the Yearbook includes information available up to mid-December 2013. A new feature this year is the inclusion of regional profiles giving an overview of each area. These offer the reader a thematic regional snapshot with a selected set of indicators. The Yearbook comprises of four chapters that cover a range of subjects such as: demographic and social indicators; economic statistics relating to trade, balance of payments and domestic prices, and national accounts; quantitative information on environment; and methodology.